Pharmacological Approach for Neuroprotection After Cardiac Arrest—A Narrative Review of Current Therapies and Future Neuroprotective Cocktail - Choudhary, Rishabh C.; Shoaib, Muhammad; Sohnen, Samantha; Rolston, Daniel M.; Jafari, Daniel; Miyara, Santiago J.; Hayashida, Kei; Molmenti, Ernesto P.; Kim, Junhwan; Becker, Lance B. (Frontiers in Medicine, 2021)
Cardiac arrest (CA) results in global ischemia-reperfusion injury damaging tissues in the whole body. The landscape of therapeutic interventions in resuscitation medicine has evolved from focusing solely on achieving return of circulation to now exploring options to mitigate brain injury and preserve brain function after CA. CA pathology includes mitochondrial damage and endoplasmic reticulum stress response, increased generation of reactive oxygen species, neuroinflammation, and neuronal excitotoxic death. Current non-pharmacologic therapies, such as therapeutic hypothermia and extracorporeal cardiopulmonary resuscitation, have shown benefits in protecting against ischemic brain injury and improving neurological outcomes post-CA, yet their application is difficult to institute ubiquitously. The current preclinical pharmacopeia to address CA and the resulting brain injury utilizes drugs that often target singular pathways and have been difficult to translate from bench to the clinical setting. Furthermore, the few combinations of therapies that have been attempted have shown mixed effects in conferring neuroprotection and improving survival post-CA. The global scale of CA damage and its resultant brain injury necessitates the future of CA interventions to simultaneously target multiple pathways and alleviate the hemodynamic, mitochondrial, metabolic, oxidative, and inflammatory processes in the brain. This narrative review seeks to highlight the current field of post-CA neuroprotective pharmaceutical therapies, both singular and combinations, and discusses the use of a multi-drug cocktail therapy as a novel approach to treat CA-mediated dysregulation of multiple pathways, enhancing survival and neuroprotection.